2010
DOI: 10.1021/jm101288t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of Aza- and Diazabiphenyl Analogues of the Antitubercular Drug (6S)-2-Nitro-6-{[4-(trifluoromethoxy)benzyl]oxy}-6,7-dihydro-5H-imidazo[2,1-b][1,3]oxazine (PA-824)

Abstract: New heterocyclic analogues of the potent biphenyl class derived from antitubercular drug PA-824 were prepared, aiming to improve aqueous solubility but maintain high metabolic stability and efficacy. The strategy involved replacement of one or both phenyl groups by pyridine, pyridazine, pyrazine, or pyrimidine, in order to reduce lipophilicity. For para-linked biaryls, hydrophilicities (ClogP) correlated with measured solubilities, but highly soluble bipyridine analogues displayed weak antitubercular activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
112
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(129 citation statements)
references
References 43 publications
(168 reference statements)
17
112
0
Order By: Relevance
“…A previous experiment conducted using the same preclinical model of TB as was used in the present work demonstrated that the efficacy of TBA-354 is superior to that of Pa when administered at the same dose and similar to that of delamanid against acute and chronic murine TB (23). Using the same low-dose aerosol infection model, these findings were extended here to demonstrate significant dose-and time-dependent bactericidal activity of TBA-354 against chronic murine TB.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…A previous experiment conducted using the same preclinical model of TB as was used in the present work demonstrated that the efficacy of TBA-354 is superior to that of Pa when administered at the same dose and similar to that of delamanid against acute and chronic murine TB (23). Using the same low-dose aerosol infection model, these findings were extended here to demonstrate significant dose-and time-dependent bactericidal activity of TBA-354 against chronic murine TB.…”
Section: Discussionsupporting
confidence: 72%
“…Because of this, several independent medicinal chemistry programs have aimed to optimize these compounds further (8). Our own medicinal chemistry program, with the Auckland Cancer Society Research Center, identified TBA-354 as a particularly potent nitroimidazo-oxazine with ADME and PK characteristics suggesting suitability for once-daily oral dosing (23). The data we report herein confirm and extend these findings.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Further structure–function relationship studies were carried out with biaryl analogs of PA-824 with the replacement of proximal, distal as well as both aryl groups with six-membered nitrogen-containing heterocycles [35]. This allowed the overall structure to be nearly linear and, hence, a better ft in the putative hydrophobic pocket of the enzyme [33].…”
Section: Structure–activity Relationships Of Anti-tubercular Nitromidmentioning
confidence: 99%